Corelation between Mother's Workers, Family Support and Health Workers with Exclusive Breastfeeding - Maulida, Maulida; Nurhamidi, Nurhamidi; Mas’odah, Siti (Journal of Local Therapy, 2023)
Exclusive breastfeeding is breast milk that is given to babies from birth for 6 months, without adding/replacing other intakes (except drugs, vitamins, minerals). Exclusive breastfeeding coverage at the Guntung Manggis Health Center in the last 3 years was 42.56% (2019), 62.88% (2020) and 35.29% (2021). There was a decrease of 27.59% in 2021. In addition, this figure has not reached the target at the Guntung Manggis Health Center, which is 65%. Objectives: To determine the relationship between mother's work, family support and health workers with exclusive breastfeeding for infants 6-12 months. Methods: Analytica observation with a cross sectional study design. Results: Exclusive breastfeeding was 33.3%. Mother works 55.6% and 44.4% does not work when the baby is 0-6 months old. Mothers with less family support are 64.4% and good are 35.6%. Mothers with less support from health workers are 64.4% and good are 35.6%. There is relationship between mother's work, family support and support from health workers with exclusive breastfeeding. Conclusions: There is a relationship between mother's work, family support and support from health workers with exclusive breastfeeding for infants aged 6-12 months in the working area of the Guntung Manggis Health Center.